Intraoperative irrigation of artificial cerebrospinal fluid and temperature of irrigation fluid for chronic subdural hematoma: a systematic review and meta-analysis - Huang, Yong-Wei; Li, Zong-Ping; Yin, Xiao-Shuang (Frontiers in Neurology, 2023)
Purpose To systematically review the different types of irrigation fluid and the different temperatures of irrigation fluid on postoperative recurrence rates in the evacuation of chronic subdural hematoma (CSDH). Methods We conducted a comprehensive search of electronic databases, including PubMed, Embase, the Cochrane Library, the China National Knowledge Infrastructure (CNKI), WanFang, the Chinese VIP Information (VIP), and China Biology Medicine (CBM), and reference lists of relevant studies to identify all eligible studies. Two reviewers independently screened the titles and abstracts for inclusion, and the full-text articles were assessed for eligibility based on predetermined inclusion and exclusion criteria. Data were extracted using a standardized form, and the quality of the studies was assessed using a risk of bias tool. Meta-analyses were performed using a fixed-or random-effects model, and heterogeneity was assessed using the I2 statistic. The primary endpoint was the postoperative recurrence rate. Results After stringent screening, a total of 11 studies were identified, including six English publications, four Chinese publications, and one Japanese publication, involving a population of 29,846 patients. Our meta-analysis provides evidence that artificial cerebrospinal fluid (ACF) could decrease the post-operative recurrence rate by 47% after the evacuation of CSDH when compared to normal saline (NS) [(odds ratio) OR 0.53, 95% confidence intervals (CI): 0.31–0.90, p = 0.02, I2 = 67%]. Besides, the irrigation fluid at body temperature could decrease the postoperative recurrence rate of CSDH by 64% when compared to room temperature (OR = 0.36, 95% CI = 0.22–0.59, p < 0.0001, I2 = 0%). Conclusion Our analysis revealed significant difference in the choice of irrigation fluid for CSDH surgery. Notably, we found that irrigation with fluid at body temperature demonstrated superiority over irrigation with fluid at room temperature, resulting in fewer instances of recurrence. This straightforward technique is both safe and widely available, providing an opportunity to optimize outcomes for patients with CSDH. Our findings suggest that the use of body-temperature NS or ACF of room temperature during operation should be considered a standard of procedure in CSDH surgery. Nevertheless, whether the different temperature of ACF could be considered a standard of procedure in CSDH surgery still need high-quality RCTs to further identify. Systematic review registration https://www.crd.york.ac.uk/prospero/; Identifier CRD42023424344.